2017
DOI: 10.1071/py16001
|View full text |Cite
|
Sign up to set email alerts
|

Case conferencing for palliative care patients – a survey of South Australian general practitioners

Abstract: Benefits of case conferencing for people with palliative care needs between a general practitioner, the person and other key participants include improving communication, advance care planning, coordination of care, clarifying goals of care and support for patient, families and carers. Despite a growing evidence base for the benefits, the uptake of case conferencing has been limited in South Australia. The aim of this study is to explore the beliefs and practice of South Australian general practitioners toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…GPs in the present study explained a number of barriers which have been reported previously, such as lack of time [16, 36, 37], lack of clarity of roles and responsibilities of GPs and other healthcare providers and services [38], poor communication between healthcare providers [16, 37, 39, 40] and poor remuneration [16, 41, 42]. In line with previous studies [43, 44], the findings also suggest that not all GPs are aware of the resources and guidelines available to support optimal, evidence-based palliative care provision.…”
Section: Discussionmentioning
confidence: 72%
“…GPs in the present study explained a number of barriers which have been reported previously, such as lack of time [16, 36, 37], lack of clarity of roles and responsibilities of GPs and other healthcare providers and services [38], poor communication between healthcare providers [16, 37, 39, 40] and poor remuneration [16, 41, 42]. In line with previous studies [43, 44], the findings also suggest that not all GPs are aware of the resources and guidelines available to support optimal, evidence-based palliative care provision.…”
Section: Discussionmentioning
confidence: 72%
“…Table 1 summarises the 21 articles identified, including data on the sample, setting, recruitment, measures, and barrier and enabler domains described. Six articles reported barriers and enablers, 29,33,35,39,40,44 13 reported barriers only, 17,[30][31][32]34,36,38,42,43,[45][46][47] and two reported enablers only. 37,41 Setting and participants…”
Section: Resultsmentioning
confidence: 99%
“…Netherlands and Northern Ireland). 17 Fourteen studies included primary care doctor participants only, 17,29,[30][31][32]34,35,37,39,40,42,45,47 three included primary care doctors and other primary care practitioners, 36,43,46 and four included specialist and primary care practitioners. 33,38,41,44 General or disease specific focus Most (n = 15) of the studies focused on general palliative care, while six focused on palliative care for people with a specific disease or condition: cancer (n = 2), 30,38 dementia (n = 1), 17 heart failure (n = 1), 36 and cirrhosis of liver (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been observed that a representative sample is not necessarily guaranteed by a high response rate 22 and our response rate is still higher or comparable to other studies that made use of online platforms as a distribution mode among primary care physicians. 23 , 24 Responding GPs were those who volunteered to participate in the survey, so selection bias cannot entirely be ruled out: it is possible that the responses given do not reliably represent the views of the majority of primary care physicians in Italy. Nonetheless, most of our questions investigated factual data rather than opinions and therefore if this bias is present it is likely to be limited.…”
Section: Discussionmentioning
confidence: 99%